Histological analysis of ankylothecodonty in Silesauridae (Archosauria: Dinosauriformes) and its implications for the evolution of dinosaur tooth attachment. Issue 2 (9th June 2021) - Mestriner, Gabriel; LeBlanc, Aaron; Nesbitt, Sterling J.; Marsola, Júlio C. A.; Irmis, Randall B.; Da‐Rosa, Átila Augusto Stock; Ribeiro, Ana Maria; Ferigolo, Jorge; Langer, Max
Abstract: Dinosaurs possess a form of tooth attachment wherein an unmineralized periodontal ligament suspends each tooth within a socket, similar to the condition in mammals and crocodylians. However, little information is known about tooth attachment and implantation in their close relatives, the silesaurids. We conducted a histological survey of several silesaurid taxa to determine the nature of tooth attachment in this phylogenetically and paleoecologically important group of archosaurs. Our histological data demonstrate that these early dinosauriforms do not exhibit the crocodilian/dinosaur condition of a permanent gomphosis, nor the rapid ankylosis that is plesiomorphic for amniotes. Instead, all sampled silesaurids exhibit delayed ankylosis, a condition in which teeth pass through a prolonged stage where the teeth are suspended in sockets by a periodontal ligament, followed by eventual mineralization and fusion of the tooth to the jaws. This suggests that tooth attachment in crocodylians and dinosaurs represent the further retention of an early ontogenetic stage compared to silesaurids, a paedomorphic trend that is mirrored in the evolution of synapsid tooth attachment. It also suggests that the dinosaur and crocodylian gomphosis was convergently acquired via heterochrony or, less likely, that the silesaurid condition represents a reversal to a plesiomorphic state. Moreover, if Silesauridae is nested within Ornithischia, a permanent gomphosis could be convergent between the two main dinosaur lineages, Ornithischia and Saurischia. These results demonstrate that dental characters in early archosaur phylogenies must be chosen and defined carefully, taking into account the relative duration of the different phases of dental ontogeny.